2020
DOI: 10.1101/2020.04.27.061952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the molecular and structural specialization of the skin basement membrane for inter-tissue interactions

Abstract: 21Inter-tissue interaction is fundamental to multicellularity. Although the basement 22 membrane (BM) is located at tissue interfaces, its mode of action in inter-tissue 23 interactions remains poorly understood, mainly because the molecular and structural 24 details of the BM at distinct inter-tissue interfaces remain unclear. By combining 25 quantitative transcriptomics and immunohistochemistry, we systematically identify the 26 cellular origin, molecular identity and tissue distribution of extracellular … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Laminins are large groups of extracellular α, β, and γ chain trimers in the basement membrane (BM) of skin. During hair follicle development, the composition of laminins in the basement membrane zone (BMZ) changes [30] . LN-332 is abundant beneath the interfollicular epidermis, whereas LN-511 is most abundant at the lower part of the hair follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Laminins are large groups of extracellular α, β, and γ chain trimers in the basement membrane (BM) of skin. During hair follicle development, the composition of laminins in the basement membrane zone (BMZ) changes [30] . LN-332 is abundant beneath the interfollicular epidermis, whereas LN-511 is most abundant at the lower part of the hair follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous fat was removed from the skin with a scalpel, and the whole skin was incubated for 30 min in 0.25% trypsin to separate into the epidermis and dermis. The dermal tissue was cut into small pieces and treated with 0.2% collagenase type I (Gibco) at 37°C for 2 hours (50). Epidermal and dermal cells were dissociated into single cells by pipetting and passing through 40-m (Falcon) and 20-m [pluriSelect (PLS)] strainers.…”
Section: Quantification Of the Blood Vessel Volume And Lengthmentioning
confidence: 99%
“…Proteins were annotated based on the matrisome category and cellular compartment classifications (Table S1). 29,32 Functional characterization of matrisome proteins as "basement membrane", "interstitial matrix", and "other" was based on 5,13,33 with additional re-annotations based on review of histology in the literature for proteins observed in this study (Table S1). Proteins were indicated as part of the elastin-microfibril axis based on literature studies ( Figure S1).…”
Section: Proteomicsmentioning
confidence: 99%